Patient decision aids in routine maternity care: Benefits, barriers, and new opportunities. Issue 1 (February 2016) - Stevens, Gabrielle; Thompson, Rachel; Watson, Bernadette; Miller, Yvette D.
Abstract: Background and aim: Participation in decision-making, supported by comprehensive and quality information provision, is increasingly emphasised as a priority for women in maternity care. Patient decision aids are tools that can offer women greater access to information and guidance to participate in maternity care decision-making. Relative to their evaluation in controlled settings, the implementation of patient decision aids in routine maternity care has received little attention and our understanding of which approaches may be effective is limited. This paper critically discusses the application of patient decision aids in routine maternity care and explores viable solutions for promoting their successful uptake. Discussion: A range of patient decision aids have been developed for use within maternity care, and controlled trials have highlighted their positive impact on the decision-making process for women. Nevertheless, evidence of successful patient decision aid implementation in real world health care settings is lacking due to practical and ideological barriers that exist. Patient-directed social marketing campaigns are a relatively novel approach to patient decision aid delivery that may facilitate their adoption in maternity care, at least in the short-term, by overcoming common implementation barriers. Social marketing may also be particularly well suited to maternity care, given the unique characteristics of this health context. Conclusions: The potential of social marketing campaigns to facilitate patient decision aid adoption in maternity care highlights the need for pragmatic trials to evaluate their effectiveness. Identifying which sub-groups of women are more or less likely to respond to these strategies will further direct implementation.